THE ELECTRONIC COURSE OF HEAT AND MASS TRANSFER - Alexander P. Solodov (Открытое образование (Москва))
The Electronic course of heat and mass transfer in power engineering is presented containing the full Electronic book as the structured hypertext document, the full set of Mathcad-documents with the whole set of educative computer models of heat and mass transfer, the computer labs, and selected educational presentations.